Comparative study of efficacy of nifedipine, nitroglycerin dermal patches and isoxsuprine as tocolytic agents in suppression of preterm labour 1-year study at navodaya medical college hospital and research centre Raichur - D., Rita; Haripriya, V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Tocolytic agents are used to reduce preterm deliveries. Very few studies documenting the comparison of tocolytic agents viz. nifedipine, nitroglycerin dermal patches and isoxsuprine. Other drugs are not used due to their adverse effects. Objective was to study and compare the safety efficacy of nifedipine, nitroglycerin dermal patches and isoxsuprine as tocolytic agents in suppression of preterm labour 1 year study. Methods: This was a prospective case control study was conducted for a period of 1 year. Total 90 cases selected to study were randomly distribute in to three treatment groups viz. A, B, and C nifedipine, nitroglycerin and isoxsuprine respectively. Subjects in all three groups were evaluated for maternal pulse rate, palpitation uterine contractions and fetal heart rate in order to assess efficacy of each drug under investigation. Results: There was no statistically significant difference in age of woman’s in three different groups. Among (100%) subjects, majority of the cases i.e. (27.8%) primi gravida followed by multi (72.2%). Side effects of nifedipine was less when compared to nitroglycerine dermal patch and isoxsuprine i/v/o of headache (8.9%), nausea (1.1%), vomiting (1.1%), tachycardia (3.3%), palpitation (3.3%), hypotension (1.1%). side effects were statistically significant different between the treatment groups. There was no statistically significant difference with respect to APGAR score at 1 minute and 5 minutes. Conclusions: Oral nifedipine was found to be superior and efficacious as tocolytic agent as compared to transdermal nitroglycerin and intravenous isoxsuprine.